IMPACT OF INTERNAL CONTROL SUCCESS ON INVESTER CONFIDENCE OF LISTED COMPANIES IN THE STOCK EXCHANGE OF THAILAND (SET) - พูนพล ณัฐวงศ์; ปลูกผลงาม ชาลินี; สภานุชาต มนชยา (RMUTT Global Business and Economics Review, 2017)
This article is about the effects of internal control success on investor confidence. The study examines the relationships between internal control success and investor confidence, where audit quality is taken as a mediator. The key participants in this study were chief executive officers (CEO) who participated in Thai listed companies. Of the surveys completed and returned, only 301 were usable. The ordinary least squares (OLS) regression analysis was employed to estimate parameters in hypotheses testing. The findings showed that internal control success, in which consists of operational effectiveness, financial reliability, and regulatory compliance, they had positive effect on audit quality significantly (p<0.1). Audit quality mediates the relationship between internal control success and investor confidence significantly (p<0.05). Therefore, a key decision for managers in all levels and functions is to focus at internal control success that can improve and develop audit quality’s effectiveness and reserves increased steeply, boosting investor confidence.